Synthesis, characterisation and biological activity of novel 4-thiazolidinones, 1,3,4-oxadiazoles and some related compounds - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (My University, 2002)
Two novel series of 4-thiazolidinone derivatives, namely 2-substituted-3-([4-(4-methoxybenzoylamino)benzoyl]amino)-4-thiazolidinones (7a-e) and 2-[4-(4-methoxybenzoylamino)benzoylhydrazono]-3-alkyl-4-thiazolidinones (5a-c) together with 2-[4-(4-methoxybenzoylamino)phenyl]-5-(substituted phenyl)amino-1,3,4-oxadiazoles (6a-c) have been synthesised as title compounds. N(1)-[4-(4-methoxybenzoylamino)benzoyl]-N(2)-substituted methylene hydrazines (3a-e) and 1-[4-(4-methoxybenzoylamino)benzoyl]-4-substituted phenyl thiosemicarbazides (4a-f) were also prepared and used as intermediate to give the title compounds. All synthesised compounds were screened for their antimycobacterial activity against Mycobacterium tuberculosis H37Rv and antimicrobial activities against various bacteria and fungi. Compounds 7a and 7b were found as the most active derivatives demonstrating 90 and 98% inhibition of mycobacterial growth of M. tuberculosis H37Rv in the primary screen at 6.25 microg mL(-1), respectively. However, level II assay revealed that the MIC values were not less than 6.25 microg mL(-1). None of the compounds showed significant antimicrobial activity against the microorganisms used whereas 3a and 7a inhibited the growth of several bacteria and fungi.
Keywords: Anti-Bacterial Agents; Microbial Sensitivity Tests; Molecular Structure; Semicarbazides; Gram-Negative Bacteria; Structure-Activity Relationship; Mycobacterium tuberculosis; Gram-Positive Bacteria; Azoles